Early Detection Patterns Of Chronic Kidney Disease Based On Differences In Individual Health Status In Kendari City: Chronic Kidney Disease - Tasnim Tasnim; Sugireng Sugireng; Imran Imran; Nur Illiyyin Akib (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: The prevalence of chronic kidney disease (CKD) was small but it continued to increase every year in Kendari City. The patients were difficult to monitor. The aim of this research is to formulate an early detection pattern for CKD based on differences in individual health status in Kendari City. Methods: This quantitative research used a cross sectional study design which was conducted at 4 Community Health Centers and 3 Hospitals in Kendari City, Southeast Sulawesi, Indonesia. Recruited 136 respondents aged between 24-70 years. Data collection by interviews with questionnaires. The dependent variable is health status, and the independent variables include behavior, psychological environment, stress and genetics. Data analysis used chi square statistical tests, crosstabulation and multinomial logistic regression. Results: There is a significant difference in drinking water consumption behavior of less than 1000 ml a day (p<0.0001, OR=1.56, B=-20.276), calorie intake of less than 1534 calories a day (p<0.05, OR=2.13, B=-19.969 ), physical activity (p<0.05, OR=5.7, B=1.735), medication adherence (P<0.01, OR=0.4,B=1.999) and psychological stress environment (p<0.0001,OR=8.6, B=2.151 ) with the respondent's health status. Meanwhile, herbal consumption behavior (p=0.195) and genetic factors (p=0.813) did not show significant differences with individual health status. Conclusion: Early detection patterns for CKD can use the variable such as less drinking water consumption in healthy people and no obedient medication in single disease group. Using variables of less daily drinking water consumption and heavy physical activity in multiple diseases group, and less drinking water consumption, less physical activity, and moderate stress in CKD group.